2002
DOI: 10.1164/rccm.2107082
|View full text |Cite
|
Sign up to set email alerts
|

Altered Breathing Pattern after Prenatal Nicotine Exposure in the Young Lamb

Abstract: Maternal smoking during pregnancy is a risk factor for sudden fetal and infant death as well as obstructive airway disease in childhood. Fetal nicotine exposure affects organ development. The aim of the present study was to investigate effects of fetal nicotine exposure on lung function in young lambs. Nine unanesthetized, awake, prenatally nicotine-exposed lambs (N) (approximate maternal dose: 0.5 mg/kg) and 12 nonexposed control lambs (C) were studied repeatedly for 5 weeks after birth using a pneumotachogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 46 publications
4
40
2
Order By: Relevance
“…27,28 In animal studies, prenatal exposure to pure nicotine indicates disturbances in the control of the cardiorespiratory system, with an increased frequency of apnea during sleep, decreased arousability and a blunted cardiorespiratory response to hypoxia, higher breathing frequency, and lower tidal volume during the neonatal period. 29,30 Our finding of an increased risk of infant apnea, as a sign of disturbed control of the cardiorespiratory system, correlates well with similar findings in animal studies of prenatal nicotine exposure. Huang et al 31 found an increased frequency of apneas during sleep in a group of prenatally nicotine-exposed rat pups during the first 2 postnatal days but not at postnatal day 6.…”
Section: Discussionsupporting
confidence: 86%
“…27,28 In animal studies, prenatal exposure to pure nicotine indicates disturbances in the control of the cardiorespiratory system, with an increased frequency of apnea during sleep, decreased arousability and a blunted cardiorespiratory response to hypoxia, higher breathing frequency, and lower tidal volume during the neonatal period. 29,30 Our finding of an increased risk of infant apnea, as a sign of disturbed control of the cardiorespiratory system, correlates well with similar findings in animal studies of prenatal nicotine exposure. Huang et al 31 found an increased frequency of apneas during sleep in a group of prenatally nicotine-exposed rat pups during the first 2 postnatal days but not at postnatal day 6.…”
Section: Discussionsupporting
confidence: 86%
“…Other examples of developmental plasticity include altered adult chemoreflexes caused by maternal separation stress (118) and prenatal nicotine exposures (12,51,70,87,207). In the pond snail Lymnaea stagnalis, preventing lung ventilation from hatching through adulthood alters mechanisms of ventilatory control in adults (92).…”
Section: Developmental Plasticitymentioning
confidence: 99%
“…The lambs were studied at the median (range) ages of 12 (5-17), 25 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and 51 (45-61) d, i.e. the earliest possible time after postoperative recovery, as late as practical with this chronic preparation, and once in between.…”
Section: Subjectsmentioning
confidence: 99%
“…the earliest possible time after postoperative recovery, as late as practical with this chronic preparation, and once in between. [Median (range) study ages for each group were 12 (5-17), 26 (24 -34), and 51 (45-61) d for LN lambs; 12 (7-16), 24 (22)(23)(24)(25)(26)(27), and 51 (47-58) d for MN lambs; and 12 (8 -13), 25 (23)(24)(25)(26)(27)(28), and 52 (49 -54) d for the control group.] The research protocol was approved by the Vanderbilt University Animal Care Committee.…”
Section: Subjectsmentioning
confidence: 99%